2018
DOI: 10.1021/acsnano.8b01826
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Rat Lung Deposition Patterns of Inhaled 20 Nanometer Gold Nanoparticles and their Quantitative Biokinetics in Adult Rats

Abstract: The increasing use of gold nanoparticles leads to a possible increase of exposure by inhalation. Therefore, we have studied the deposition patterns of inhaled 20 nm gold nanoparticles (AuNP) in 7-90 day old rats and their biokinetics in 60 day old ones. Wistar-Kyoto rats inhaled intratracheally 20 nm Au-radiolabeled AuNP by negative pressure ventilation over 2 h. Immediately afterward lungs were excised, inflated and microwave dried. AuNP deposition was analyzed by single-photon emission computed tomography, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 75 publications
5
104
2
Order By: Relevance
“…Furthermore, structural details obtained at high resolution in 3D are very important for our understanding of ventilation and particle deposition. E.g., they are important for simulations of acinar airflow and particle deposition (Sznitman et al 2010 ; Henry et al 2012 ; Tsuda et al 2008 ; Hofemeier et al 2018 ) or for the correlation between the amount of the deposition of inhaled particles in rat lungs and the size of the airspaces (Semmler-Behnke et al 2012 ; Kreyling et al 2018 ). Therefore, the application of modern cutting edge imaging and quantitative histological techniques advanced our anatomical and physiological knowledge significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, structural details obtained at high resolution in 3D are very important for our understanding of ventilation and particle deposition. E.g., they are important for simulations of acinar airflow and particle deposition (Sznitman et al 2010 ; Henry et al 2012 ; Tsuda et al 2008 ; Hofemeier et al 2018 ) or for the correlation between the amount of the deposition of inhaled particles in rat lungs and the size of the airspaces (Semmler-Behnke et al 2012 ; Kreyling et al 2018 ). Therefore, the application of modern cutting edge imaging and quantitative histological techniques advanced our anatomical and physiological knowledge significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, existence of NPs in the esophagus indicated that NPs can be cleared within a few minutes towards the digestive tract by either mucociliary clearance or coughing ( Figure 3d and Video S6). 38 Quantitative analysis of dose and regional deposition of inhaled MF It became evident that each lung had a different autofluorescence level due to differences in the optical properties of the lungs, in lung volume, and LSFM instrument uncertainties (despite the same settings of LSFM were used for all lungs). Here, the average of measured total fluorescence intensity from blank lungs was (11.1 ± 3.33) ×10 10 and the relative high standard deviation of 30.2% demonstrates the variations in tissue-induced fluorescence due to lung and instrument variations.…”
Section: D Lung Mapping Of Mf Distribution With Cellular Resolution mentioning
confidence: 99%
“…[56][57][58][59][60] For example, the occurrence of side effects may be delayed, given that some nanotechnology platforms, such as nanogold, can accumulate in tissues and persist longer than traditional medicines. 61 As a result, some side effects might not be captured during the trial itself or even during the first few years of postapproval long-term safety monitoring. Although clinical trials are often powered to detect strong early negative safety signals, years of experience with medications is required before clinicians can fully understand the long-term effects of exposure.…”
Section: Ethical Considerations In Nanomedicinementioning
confidence: 99%